2021
DOI: 10.3390/ijms22083933
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal Aβ-Binding Proteins Identified by “In Silico” Analysis Represent Putative Blood-Derived Biomarker Candidates for Alzheimer´s Disease

Abstract: The potential of exosomes as biomarker resources for diagnostics and even for therapeutics has intensified research in the field, including in the context of Alzheimer´s disease (AD). The search for disease biomarkers in peripheral biofluids is advancing mainly due to the easy access it offers. In the study presented here, emphasis was given to the bioinformatic identification of putative exosomal candidates for AD. The exosomal proteomes of cerebrospinal fluid (CSF), serum and plasma, were obtained from three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 157 publications
0
20
0
2
Order By: Relevance
“…In addition, it was shown that C4BPα limits the complement activation by Aβ and/or death cells in AD brains, possibly protecting the neuronal environment from immune activation [56]. Moreover, a previous bioinformatic analysis by our group [29] identi ed both AACT and C4BPα as Aβ-binding proteins in the exosomal proteome, constructed by the overlap of serum-, plasma-and CSF-exosomal proteomes available in databases namely EXOCARTA, Vesiclepedia or EVpedia. Taken together, we hypothesized that AACT and C4BPα could represent putative AD exosomal biomarker candidates, and thus both markers were tested in serum-derived exosomes from Control and AD cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it was shown that C4BPα limits the complement activation by Aβ and/or death cells in AD brains, possibly protecting the neuronal environment from immune activation [56]. Moreover, a previous bioinformatic analysis by our group [29] identi ed both AACT and C4BPα as Aβ-binding proteins in the exosomal proteome, constructed by the overlap of serum-, plasma-and CSF-exosomal proteomes available in databases namely EXOCARTA, Vesiclepedia or EVpedia. Taken together, we hypothesized that AACT and C4BPα could represent putative AD exosomal biomarker candidates, and thus both markers were tested in serum-derived exosomes from Control and AD cases.…”
Section: Discussionmentioning
confidence: 99%
“…For further analyses, exosomal proteomes obtained through MS (list of gene names from proteins identi ed) were overlapped with an 'in silico' serum-derived exosomal gene list. This list was collated using public databases, namely Vesiclepedia, EVpedia and Exocarta and complemented following a literature review on exosomal AD related proteins [11,29]. More than 70% of the exosomal proteins identi ed by MS and isolated either with ExoQ or ExoS were also present in the serum-derived exosomal gene list, reinforcing the exosomal nature of the samples (Fig.…”
Section: Go Analyses Of Evs From Controls and Ad Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, exosomes have attracted considerable interest in the study of brain diseases, such as Alzheimer's disease, Parkinson's disease, stroke, and traumatic brain injury, due to their critical importance in the disease process and potential value for clinical application. The role and molecular mechanisms of exosomes carrying proteins related to the brain diseases [amyloid precursor protein (APP), α-synuclein (α-syn), mHtt, PrPsc] have been emphatically explored (Hartmann et al, 2017 ; Leblanc et al, 2017 ; Wang J. K. T. et al, 2017 ; Hill, 2019 ; Li B. et al, 2020 ; Pan et al, 2020 ; Perez-Gonzalez et al, 2020 ; Singh and Muqit, 2020 ; Tsunemi et al, 2020 , 2021 ; Ananbeh et al, 2021 ; Soares Martins et al, 2021a ). Notably, their ability to transport cargo is a key mechanism involved in the spread of disease.…”
Section: Introductionmentioning
confidence: 99%